2011
DOI: 10.3904/kjim.2011.26.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Somatostatinoma: A Case Report and Review

Abstract: Somatostatinomas are rare functioning carcinoid tumors that usually arise in the pancreas and duodenum. They are seldom associated with typical clinical symptoms; their diagnosis is confirmed only by histological and immunohistochemical studies and the presence of specific hormones. Two distinct clinicopathological forms of somatostatinoma exist: duodenal and pancreatic somatostatinomas. Clinically, compared to pancreatic somatostatinomas, duodenal somatostatinomas are more often associated with nonspecific sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
(18 reference statements)
0
20
0
Order By: Relevance
“…Whipple’s operation with regional lymphadenectomy should be considered for more aggressive or larger tumours. Radiation and chemotherapy are also treatment options, but most metastatic NETs are unresponsive to chemotherapy 33–37. For tumours <1 cm, there is no consensus regarding management, although endoscopic excision is considered a reasonable approach because of the low incidence of metastasis and lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Whipple’s operation with regional lymphadenectomy should be considered for more aggressive or larger tumours. Radiation and chemotherapy are also treatment options, but most metastatic NETs are unresponsive to chemotherapy 33–37. For tumours <1 cm, there is no consensus regarding management, although endoscopic excision is considered a reasonable approach because of the low incidence of metastasis and lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatinomas may be sporadic (93,1%) or familial (6,9%) in association with neurofibromatosis tipe 1(NF1), multiple endocrine neoplasia type 1 (MEN 1) and Von Hippel-Lindau syndrome [3][4][5] . Unlike pancreatic somatostatinomas which are supposed to present with diabetes mellitus, cholelithiasis and steatorrhea also known as the "somatostatinoma syndrome", duodenal somatostatinomas produce local symptoms such as jaundice, abdominal pain and gastrointestinal bleeding or are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Other sites of somatostatinomas include the duodenum (19%), the papilla of Vater (3%) the small intestine (3%), bronchus and liver 2 . Unlike pancreatic somatostatinoma which generaly produces a clinical syndrome (diabetes, steatorrhea, hypohloridria, dyspepsia) duodenal somatostatinoma may be completely asymptomatic 3,4 . In view of the rarity and the significance of the histologic diagnosis, we report a patient with malignant duodenal somatostatinoma with lymph node metastases that has been treated by surgery.…”
Section: Introductionmentioning
confidence: 99%
“…No data supports the benefit of adjuvant chemotherapy for the treatment of metastatic somatostatinoma, although few small case series reported that the synthetic somatostatin analogue octreotide, at 0.5 mg subcutaneously per day, had some benefits, including reduced diarrhea and other somatostatinoma symptoms, and stabilised tumor growth. Some studies on somatostatinoma reported no benefit from this treatment, which might be from a different subtype of somatostatin produced from the tumor 14,15. The overall 5-year survival for metastatic somatostatinoma was reported at approximately 40%, whereas that for small nonmetastatic lesions is 100% 15…”
Section: Discussionmentioning
confidence: 99%